Urban stormwater management for property development projects in Selangor and Negeri Sembilan [compact disc] - 243917 Mohd. Yazid Abdullah (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2006